2014
DOI: 10.1002/rcs.1600
|View full text |Cite
|
Sign up to set email alerts
|

Development of a robotic system with six-degrees-of-freedom robotic tool manipulators for single-port surgery

Abstract: Our robotics allowed the operator to adjust the vision field intuitively. The tool manipulator approached and resected diseased tissue precisely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Each arm usually possesses four to eight DoFs so that enough workspace and distal dexterity could be generated. Actuation schemes of the arm joints include cables (7,(16)(17)(18)(23)(24)(25), embedded servo motors (10,11,(26)(27)(28)(29), flexible shafts (12,14), linkages (15), and continuum mechanisms (19)(20)(21)(22)30). The characteristics could be summarized as follows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each arm usually possesses four to eight DoFs so that enough workspace and distal dexterity could be generated. Actuation schemes of the arm joints include cables (7,(16)(17)(18)(23)(24)(25), embedded servo motors (10,11,(26)(27)(28)(29), flexible shafts (12,14), linkages (15), and continuum mechanisms (19)(20)(21)(22)30). The characteristics could be summarized as follows.…”
Section: Discussionmentioning
confidence: 99%
“…A flexible endoscope, a ;6 mm 3-DoF manipulation arm for cautery, and a ;8 mm 5-DoF manipulation arm for gripping are integrated. A double-screw-drive mechanism (13), which consists of parallel screws and universal joints, (14). The diameter of the sheath was reduced to 25 mm and both manipulation arms possess six DoFs and a diameter of 8 mm (Figure 2c).…”
Section: Robotic Systems For Splmentioning
confidence: 99%
“…The success of laparoscopic and endoscopic surgical robots had stimulated worldwide atentions in surgical robot research, for instance, the laparoscopic telesurgical RAVEN robot [104,105], the Magellan endovascular robot [106], snake-like surgical robots [107,108], MRI-compatible surgical robots [109,110], single-incision laparoscopic robots [111][112][113][114][115][116], and endoscopic robots [117][118][119][120][121].…”
Section: Global Atention and Trends In Surgical Robotsmentioning
confidence: 99%
“…The third observation is the technology used in the new systems. All of the cited systems used cable transmission to remotely drive the robotic end-efector except one design that utilized a screw-drive [117]. To create the cable-pulling motion, various techniques were employed; the majority used electric motor [103, 106-109, 113-115, 119-121], while others used shape-memory alloy [116,118], pneumatics [109], piezoelectric actuator [110], and magnetics [117].…”
Section: Global Atention and Trends In Surgical Robotsmentioning
confidence: 99%
“…Content may change prior to final publication. master-slave single-port surgical robot that has a 25mm flexible shaft, two 8mm 6-DoF instruments, and a camera that can be manipulated to adjust the field of view [8]. In previous work, the authors reported a multitasking robotic platform for single-port access surgery in [9].…”
Section: Introductionmentioning
confidence: 99%